2016
DOI: 10.1016/j.jpsychires.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA network is altered in anterior cingulate cortex of patients with unipolar and bipolar depression

Abstract: MicroRNAs (miRNAs) are small, non-coding RNAs acting as post-transcriptional regulators of gene expression. Though implicated in multiple CNS disorders, miRNAs have not been examined in any psychiatric disease state in anterior cingulate cortex (AnCg), a brain region centrally involved in regulating mood. We performed qPCR analyses of 29 miRNAs previously implicated in psychiatric illness (major depressive disorder (MDD), bipolar disorder (BP) and/or schizophrenia (SZ)) in AnCg of patients with MDD and BP vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 107 publications
1
32
0
1
Order By: Relevance
“…In a postmortem study, miR-132 and miR-212 were initially identified as differentially expressed in bipolar disorder [22]. In patients with postpartum psychosis, miR-212 was found to be decreased in monocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…In a postmortem study, miR-132 and miR-212 were initially identified as differentially expressed in bipolar disorder [22]. In patients with postpartum psychosis, miR-212 was found to be decreased in monocytes [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study failed to detect a change in miR-34a in the anterior cingulate in MDD but did report an increase in that miRNA in their cerebellum [62]. Changes in miR-34a were only found in the cerebellum from drug naive subjects and, therefore, differences in subject drug treatment status could account of the discrepancies between in the two studies [44,62].…”
Section: Mir-34amentioning
confidence: 99%
“…Moreover, amongst these miRNA are a few miRNA that could be making an important contribution to disrupting major signalling pathways in in MDD and BD. As such, several studies have reported altered expression of miR-124 and miR-34a miRNA in both the CNS and the periphery of subjects with MDD and BD and evidence suggests they regulate biochemical and cellular pathways thought to be relevant the neurological dysfunction in mood disorders [43][44][45]. Furthermore, given the difficulties in modelling the clinical profile of mood disorders in animals, altered levels of the primate specific miRNA, miR-1202, in MDD suggest this miRNA may be important in understanding MDD as a clinical disorder of humans [46].…”
Section: Micro Rna In Mood Disordersmentioning
confidence: 99%
See 2 more Smart Citations